OUT OF POCKET EXPENDITURE ON THALASSEMIA MAJOR AND ITS IMPLICATIONS ON THE HOUSEHOLD ECONOMICS - Qamar, Mariam Khan; Shaikh, Babar Tasneem (Journal of Ayub Medical College Abbottabad, 2022)
Background: Pakistan faces a considerable burden of disease with regard to inherited blood disorder, i.e., Thalassemia Major. Its economic implications are least studied before, particularly when it comes to ascertaining a household’s out of pocket expense on treating the disease. This study was carried out to understand the current estimate of Out-of-pocket expenditure (OOP) expense and its implications on the household and livelihood, while seeking treatment for a child suffering from thalassemia. Methods: It was a descriptive cross-sectional study of 3 months’ duration. Patients were selected from Fauji Foundation Hospital (FFH) and Pakistan Institute of Medical Sciences (PIMS), through. The descriptive quantitative analysis and inferential analysis was carried through purposive sampling. Results: Treatment expense of entitled patients from FFH hospital (a public hospital which offers entitlement to the families of retired army personnel) was compared with that of non-entitled patients coming to PIMS (a public sector general hospital). Total expense incurred on treatment by the end of the month was PKR. 5000-10,000 (USD31-62) in FFH, while at PIMS, the total expense incurred on treatment by the end of the month was around PKR 80,000 (USD500). Around 37% families having an average monthly income of PkRs25000 (USD150) only, sold their livelihoods, 31% compromised on their children’s education expenses and 23% percent curtailed the health expenses of the other children. Conclusion: The out-of-pocket expenditure on treating TM is quite high and compels the families to borrow money and sell or mortgage their property, which puts a great deal monetary pressure given their socio-economic status. A practical solution would be to cover these families under the health safety net supported by the government.